Characterization and Pharmacological Efficacy of Silver Nanoparticles Biosynthesized Using the Bark Extract of Garcinia Kola - Sunday Adewale Akintelu; Seyifunmi Charles Olugbeko; Femi Adekunle Folorunso; Abel Kolawole Oyebamiji; Aderonke Similoluwa Folorunso (Journal of Chemistry)
The delinquent peril of bacterial infections affecting human kind is becoming unbearable. This study was embarked on to investigate the antimicrobial activity of biosynthesized silver nanoparticles (AgNPs) using Garcinia kola bark extract against some bacteria strains. Fresh barks of Garcinia kola were obtained from the “Gbeleju” farm land in Irele town in Ondo state region of Nigeria. Exactly 0.4 g of previously pulverized bark of Garcinia kola was immersed into 20 mL of distilled water and heated at 60–70°C for 10 minutes yielding the extract. The biosynthesized nanoparticle was characterized with UV spectroscope, Fourier infrared spectroscope (FTIR), transmission electron microscope (TEM), and energy dispersive X-Ray analyzer (EDX). Then, 0.2 g of the silver nanoparticles was dissolved in 2 ml of water to yield 100 mg/ml of the stock solution which was further diluted for the antibacterial analysis via the disc diffusion method. The result obtained from the analytical characterization of the biosynthesized silver nanoparticles revealed a spherical particle shape, particle size in the range of 12.23 to 27.90 nm with an average size of 20.07 nm via TEM analysis. The FTIR analysis confirmed the presence of -OH functional group for the stabilization of the silver nanoparticles formed due to the broad peak at wavelength 3324.52 and 3344.21 cm−1. The EDX analysis revealed carbon, nitrogen, oxygen, aluminum, potassium, copper, and silver as the elements present in the nanoparticles. Results obtained from the antibacterial screening of the biosynthesized AgNPs showed inhibitory potential that are capable of obstructing the growth of the test bacteria. This investigation ascertained the biosynthesized AgNPs as a remedy for curing bacterial infections and also a promising source for novel antibacterial agent.